Effects of Experience Quality and Perceived Value on Tourist Satisfaction And Behavioral Intention In Prambanan Temple - Hussein Gibreel Musa; Fatikha Rizdiana Dewi; Indah Fatmawati (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
This purpose of this study is to analyze the effect of experience quality, perceived value and satisfaction on behavioral intentions in Yogyakarta tourism. Settings used in this study is prambanan temple which is located on the border of Yogyakarta and Central Java. Prambanan temple managed by PT. Taman Wisata Candi Borobudur, Prambanan and Ratu Boko (Persero). This research is a kind of quantitative research conducted by the survey. Data collection techniques used in this study by questionnaire. Sample of this study was prambanan temple tourist and fulfill the criteria by the researchers. The number of respondents used in this study were 179 respondents. Sampling technique used is non probability sampling with purposive sampling method. The data analysis in this study were descriptive statistics and SEM (structural Equation modeling). The results of this study showed overall the hypotheses proposed in this study has a significant and positive influence. For indirect effects, perceived value in this study does not mediate the relationship between experience quality and satisfaction.